Analisis Kualitas Aspal Pertamina Dan Aspal PG 70 Berdasarkan Uji Penetrasi Menggunakan SNI 2456-2011 - Wibisono, R Endro; Yuantika, Risma (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
A road must meet the criteria of being safe and comfortable for its users. One type of road pavement that is commonly used in Indonesia is flexible road pavement, where the main material of flexible pavement is asphalt. In this study, Pertamina asphalt and PG 70 asphalt were used, where the aim of this research was to determine the quality of these two asphalts. The method used in this research is laboratory testing in accordance with the SNI 2456 - 2011 penetration test guidelines. After testing, the penetration value for asphalt penetration was 61, while PG 70 asphalt was 48, which means that Pertamina asphalt is more flexible than PG 70 asphalt. The stability of the second This asphalt is not much different, but the stability of PG 70 asphalt is higher, which indicates that this asphalt is suitable for use in traffic with medium or heavy vehicle intensity. In Indonesia, the use of Pertamina asphalt is more dominant than PG 70 asphalt because Pertamina asphalt is asphalt oil produced by PT. Pertamina. Meanwhile, PG 70 asphalt is still rarely used because this modified asphalt has problems with the mixture. The two asphalt test objects have slight differences in appearance and texture. Petamin asphalt has a dark black, shiny appearance and a more flexible texture. Meanwhile, PG 70 asphalt is dark black in color but is no more shiny than Pertamina asphalt, apart from that, PG 70 asphalt has a harder texture.